2018
DOI: 10.1007/s13205-018-1488-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mineral phosphate solubilizing and plant growth promoting bacteria from termite soil of arid region

Abstract: Five highly efficient phosphate solubilizing bacteria, viz., Pantoea sp. A3, Pantoea sp. A34, Kosakonia sp. A37, Kosakonia sp. B7 and Bacillus sp. AH9 were isolated from termitorial soils of Sanjivani island of southern Maharashtra, India. These isolates were characterized and explored for phosphate solubilization and plant growth promotion. Among these, Bacillus sp. AH9 showed highest phosphate solubilization index (3.5) and solubilization efficiency (250%) on Pikovskaya agar. Interestingly, Pantoea sp. A34 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 49 publications
2
21
0
8
Order By: Relevance
“…The bacterial isolates recovered in this study revealed higher affinity to solubilize phosphorus (117 bacterial isolates) than potassium. Chakdar et al (2018) stated that termite mound soils hold higher amount of phosphorus when compared to the surrounding soils due to the presence of highly efficient phosphate-solubilizing bacteria. Ability of these phosphate solubilizing bacteria to solubilize inorganic and organic phosphorus is seen as significant features for increasing soil fertility and their use as inoculants concurrently can increase plant phosphorus uptake and increase crop yield (Hameedaa et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial isolates recovered in this study revealed higher affinity to solubilize phosphorus (117 bacterial isolates) than potassium. Chakdar et al (2018) stated that termite mound soils hold higher amount of phosphorus when compared to the surrounding soils due to the presence of highly efficient phosphate-solubilizing bacteria. Ability of these phosphate solubilizing bacteria to solubilize inorganic and organic phosphorus is seen as significant features for increasing soil fertility and their use as inoculants concurrently can increase plant phosphorus uptake and increase crop yield (Hameedaa et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Within genus Kosakonia this ability was previously reported only in the strain Kosakonia sp. A37 ( Chakdar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the transformation of glucose to gluconic acid through the intermediate formation of glucono-1,5-lactone occurs in the periplasmic space (Yamada et al 2003) and this process depends on the activity of a pyrroloquinoline quinone (PQQ)-linked membrane-bound glucose dehydrogenase, and the pqqABCDEF operons are essential for PQQ biosynthesis (Andreeva et al 2011). Chakdar et al (2018) reported that Kosakonia and Bacillus isolated from termite mound soils produced both 2-keto gluconic acid and gluconic acid during Indole acetic acid (IAA) is another significant hormone that is needed by plants to ensure proper growth (Guo et al 2018). Termite mound and adjacent soil metagenomes contained ipdC and ppdC that code for Indole-3-pyruvate decarboxylase and phenylpyruvate decarboxylase respectively, enzymes that produce IAA from tryptophan (Sugawara et al 2015).…”
Section: Discussionmentioning
confidence: 99%